Scheffer/Schachtschabel Soil Science - Blume, Hans-Peter; Brümmer, Gerhard W.; Fleige, Heiner; Horn, Rainer; Kandeler, Ellen; Kögel-Knabner, Ingrid; Kretzschmar, Ruben; Stahr, Karl; Wilke, B.-Michael (Springer Berlin Heidelberg : Imprint: Springer, 2016)
The soils are fundamental to our existence, delivering water and  nutrients to plants, that feed us. But they are in many ways in danger and their conservation is therefore a most important focus for science, governments and society as a whole. A team of world recognised researchers have prepared this first English edition based on the 16th European edition. • The precusors and the processes of soil development • The physical, biological and chemical properties of soils • Nutrients and  Polluntants • The various soil classifications with the main focus on the World Reference Base for Soil Resources (WRB) • The most important soils and soil landscapes  of the world • Soil Evaluation Techniques • Basic Principles of Soil Conservation Whoever works with soils needs this book.